Synthesis, structural characterization, and optical properties of benzo[f]naphtho[2,3-b]phosphoindoles - Matsumura, Mio; Teramoto, Takahiro; Kawakubo, Masato; Kawahata, Masatoshi; Murata, Yuki; Yamaguchi, Kentaro; Uchiyama, Masanobu; Yasuike, Shuji (Beilstein Journal of Organic Chemistry, 2021)
Phosphole-fused π-conjugated acenes have been attracting interest because of the attractive features of the phosphole moiety, such as fluorescence and chemically modifiable properties. Herein, 6-phenyl-6H-benzo[f]naphtho[2,3-b]phosphoindole was prepared by reacting dichlorophenylphosphine with a dilithium intermediate derived from 3,3′-dibromo-2,2′-binaphthyl. Various derivatives, such as a phospholium salt and a borane–phosphole complex with functional groups on the phosphorus atom were synthesized using the obtained phosphole as a common starting material. Single-crystal X-ray analysis of the parent benzo[f]naphtho[2,3-b]phosphoindole revealed that the pentacyclic ring is almost planar. Fluorescence spectroscopy data showed that the phosphole derivatives, such as phosphine oxide and the phospholium salt and borane complex exhibited photoluminescence in chloroform.
Keywords: benzo[f]naphtho[2,3-b]phosphoindole; molecular structure; optical property; phosphorus